The role of interleukin 16 in the pathogenesis of selected skin diseases - Dorota Purzycka-Bohdan; Bogusław Nedoszytko; Michał Żmijewski; Aneta Szczerkowska-Dobosz; Monika Zabłotna; Roman Nowicki (Termedia Publishing House, 2014)
Interleukin-16 (IL-16) is a proinflammatory cytokine with a pleiotropic impact on cells of the immune system. Based on its biological properties including activation of CD4+ T cell migration and proliferation and also stimulation of proinflammatory cytokine synthesis, it could be postulated that IL-16 may play an important role in the pathogenesis of many diseases associated with immunological disturbances. Interleukin-16 acts as a chemoattractant not only for T CD4+ lymphocytes, but also for other cells, which have specific receptors on their surface. Moreover, IL-16 acts as a cell cycle regulator. This cytokine is produced by cells of the immune system, i.e. T CD4+ and T CD8+ lymphocytes, eosinophils, mast cells, dendritic cells and also fibroblasts and epithelial cells. The mechanism of action of IL-16 may suggest its significant role in the pathogenesis of skin disorders associated with an inflammatory reaction and infiltration composed of T CD4+ lymphocytes. Both this interleukin and anti-IL-16 antibodies may be useful in diagnosis and therapy of many skin diseases. Further detailed studies on the release of IL-16 and its biological functions are needed to reveal the role of this cytokine in the complex immunological process. The aim of this article is a current literature review of the relationship between IL-16 and the development of selected skin diseases: atopic dermatitis, systemic lupus erythematosus, bullous pemphigoid, cutaneous T-cell lymphomas and psoriasis.